2021
DOI: 10.1002/jdd.12854
|View full text |Cite
|
Sign up to set email alerts
|

“It's just inappropriate”: Harassment of dental students by patients

Abstract: Introduction:Harassment is an issue that occurs in all workplaces and institutions. Due to increased exposure to patients, higher rates of harassment are experienced in health care systems. Health care workers need to form a professional relationship with patients to attend to their health care needs; however, harassment by patients can disrupt this relationship and have detrimental physical, mental, and emotional impacts on the health practitioner. Objective: The purpose of this study was to examine the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Among these, 53% had experienced verbal harassment and 19% had experienced sexual harassment. Patients sending pictures of their private body parts, making racial jokes and insults, and raising their voices were reported by these students [ 19 ]. In the present study, 6.2% of study participants reported being sexually harassed and 50.41% had experienced verbal harassment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 53% had experienced verbal harassment and 19% had experienced sexual harassment. Patients sending pictures of their private body parts, making racial jokes and insults, and raising their voices were reported by these students [ 19 ]. In the present study, 6.2% of study participants reported being sexually harassed and 50.41% had experienced verbal harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Liaw, R.D.Y. et al, reported that students who had experienced patient harassment lost interest in social life and their will to continue studying dentistry [ 19 ]. These findings were similar to the results of a study conducted by Tee, S. et al, in which 81.1% of nursing students from the United Kingdom reported being psychologically and emotionally affected by patients’ aggressive behavior [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation